Misuse of Consumer Personal Data Through Illegal Fintech Peer To Peer Lending - Syaiful, Rivasya Dinda; Sugiyono, Heru (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This research examines the misuse of consumer personal data through illegal Fintech Peer To Peer Lending. The aim of this research is to determine aspects related to Peer-to-peer lending Fintech Companies with a focus on the problem of misuse of consumer data. By providing an in-depth overview of forms of data misuse, as well as analyzing the legal responsibilities of illegal peer to peer lending fintech providers who are involved in misuse of consumer data. The research focus based on the background in this research is; 1) What are the forms of misuse of consumer data through illegal fintech peer to peer lending according to decision number; 438/Pid.Sus/2020/PN Jkt.Utr. 2) What is the legal responsibility of individuals managing illegal peer to peer lending fintech who misuse consumer personal data according to Decision Number; 438/Pid.Sus/2020/PN Jkt.Utr. This research uses a type of normative juridical research using qualitative methods and analytical descriptive approaches. So that the analysis can be carried out, the author first collects materials that are appropriate to the legal issue to be studied. The research results show that illegal fintech operators often misuse consumer data by involving third parties who do not have official certification, giving rise to intimidation, threats and defamation of consumers. In addition, the practice of requesting consumer consent to access personal data in violation of certain regulations was also exposed. The conclusion of this research confirms that this act can be subject to criminal sanctions as stated in the court decision. It is hoped that legal enforcement of this practice can be an effective step to protect consumer data and prevent abuse in the peer-to-peer lending fintech industry. Keywords: Misuse of personal data; illegal fintech peer-to-peer lending; positive law in Indonesia.